Factores socios ambientales y su influencia en la bronquitis aguda en niños de 6 meses - 5 años, consulta externa del Hospital Básico de Baba, 2018 - Franco Plaza, Victor Manuel (2019)
This investigation is based on the appearance of acute bronchitis, which is the inflammation of the acute type of the respiratory tract, which causes respiratory distress. The objective of this research is to determine what are the intermediate factors and their influence on bronchitis. Acute in children of 6 months - 5 years in the outpatient clinic of the Basic Hospital of Baba 2018, with the purpose of reducing the incidence of this pathology in the child population. The methodology that is implemented in this research is of a descriptive, transversal retrospective type, where a population of 189 children is considered, of which 85. The results were, 82% unknown of the pathology, 40%, had, repetitive pictures, 93%, 82% do not recognize the signs and symptoms of the pathology, 62% do not know how to proceed with the pathology, 87 It is not known how the pathology originates. It has been concluded that the pathology is more than the lack of information. The pathology has become a group of parents, 82% of these unknown pathology, while only 18% is in the knowledge of it. . The main recommendation is to encourage parents to avoid automation and advise them to resort to health centers, to avoid complications of the pathology.